2020
DOI: 10.1111/acel.13163
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP‐ribose) polymerase 1 inhibition prevents neurodegeneration and promotes α‐synuclein degradation via transcription factor EB‐dependent autophagy in mutant α‐synucleinA53T model of Parkinson's disease

Abstract: Poly (ADP‐ribose) polymerase 1 (PARP1) is a master regulator of diverse biological processes such as DNA repair, oxidative stress, and apoptosis. PARP1 can be activated by aggregated α‐synuclein, and this process in turn exacerbates toxicity of α‐synuclein. This circle is closely linked to the evolution of Parkinson's disease (PD) that characterized by progressive neurodegeneration and motor deficits. Here, we reported the PARP1, as a novel upstream molecular of transcription factor EB (TFEB), participates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…Further, genetic deletion of PARP-1 (or its pharmacological inhibition) diminished ASN toxicity and loss of DA neurons, and also improved behavioral performance [93]. In another study, PARP-1 inhibition by Veliparib was found to attenuate ASN accumulation, protect DA neurons, and improve the motor ability of transgenic mice carrying the A53T mutation [94]. An important event connected with PARP-1 is its role in promoting nuclear factor kappa B (NF-κB) activation, as well as downstream pro-inflammatory mediator expression in microglia [95].…”
Section: Asn-protein Network and Its Role In Neurotoxicitymentioning
confidence: 99%
“…Further, genetic deletion of PARP-1 (or its pharmacological inhibition) diminished ASN toxicity and loss of DA neurons, and also improved behavioral performance [93]. In another study, PARP-1 inhibition by Veliparib was found to attenuate ASN accumulation, protect DA neurons, and improve the motor ability of transgenic mice carrying the A53T mutation [94]. An important event connected with PARP-1 is its role in promoting nuclear factor kappa B (NF-κB) activation, as well as downstream pro-inflammatory mediator expression in microglia [95].…”
Section: Asn-protein Network and Its Role In Neurotoxicitymentioning
confidence: 99%
“…Combined with the results of Cannabidiol's effect on oxidative stress, we demonstrated that Cannabidiol can reduce oxidative stress damage, eliminate the increase in misfolded α-synuclein and other proteins, induce autophagy, and alleviate mitochondrial dysfunction. Mitochondrial biogenesis is a key process in the maintenance of mitochondrial mass, SIRT1 is the main regulator of mitochondrial biogenesis (Mao et al, 2020). The increase of SIRT1 has been considered as a therapeutic strategy for PD, previous research showed that SIRT1 has neuroprotective effects in both in vivo and in vitro PD models (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial biogenesis is a key process in the maintenance of mitochondrial mass, SIRT1 is the main regulator of mitochondrial biogenesis ( Mao et al, 2020 ). The increase of SIRT1 has been considered as a therapeutic strategy for PD, previous research showed that SIRT1 has neuroprotective effects in both in vivo and in vitro PD models ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As seen with ATM kinase levels, PARP1 levels beyond a certain threshold may be detrimental for certain agerelated co-morbidities. One such example is where PARP1 inhibition initiated prevention of neurodegeneration seen during Parkinson's disease, by restoring degradation of alphasynuclein [231]. There are other examples where PARP1 inhibition alleviated age-related cellular [156] and tissue dysfunction [232] and could be a potential therapeutic option for osteoporosis.…”
Section: Future Directionsmentioning
confidence: 99%